Analisis Studi Kelayakan Bisnis ppada Usaha Manufaktur Konveksi Moju di Tinjau dari Aspek Biaya dan Produksi - Rofiqoh, Nadya Aulia; Sawalni, Sawalni; Karlina, Neng Cica; Husain, Nanda Baihaqi; Luthfiyah, Nida Hulwa; Abdullah, M Zidan; Yelipele, Ipan (INDO PUBLISHING, 2026)
This study aims to analyze the business feasibility of Moju Convection manufacturing company based on financial and operational aspects. The research uses a descriptive quantitative approach with data collected through interviews, observations, and documentation. The analysis focuses on cost structure, revenue, cash flow, and payback period as well as production capacity and quality control. The results show that Moju Convection has stable fixed and variable costs, high monthly revenue, positive annual cash flow, and a payback period of approximately one year. Operationally, the company demonstrates efficient production flow and low defect rates after management improvements. Therefore, the business is considered feasible to operate and to be developed sustainably.